RETRACTED: Detection and Determination of Captopril Using Silver Nanoparticles Based Colorimetric Method - Anida Hasna Rahmatika; Mohammad Alauhdin (Journal of Science and Technology Research for Pharmacy, 2024)
This article has been retracted. Reason: This article has been retracted following a mutual agreement between the authors and the journal that the manuscript should not proceed to publication. The retraction is issued to ensure the integrity of the academic record Basic Health Research (Riskesdas) in 2018 showed an increase in the prevalence of hypertension in Indonesia. Captopril is one of the antihypertensive drugs that is often prescribed because it is affordable and effective in lowering blood pressure, but captopril also has several side effects. Therefore, the development of sensitive, simple, rapid and cost-effective analytical techniques for the determination of captopril is urgently needed. This research aims to develop a colorimetric detection of captopril using silver nanoparticles and analyze its performance in measuring the captopril in tablet samples. The parameters studied include linearity, sensitivity, accuracy and precision. The results of the research show that silver nanoparticles can be used for qualitative detection of captopril which is characterized by a color change and absorbance decrease of the sample solution. The results of the performance test of the developed method showed good results. The linearity test showed a correlation coefficient (r) of 0.9915 with the regression equation obtained was y = 0.263x + 129.26. The limit of detection (LOD) value is 0.0206 ppm and the limit of quantitation (LOQ) is 0.0687 ppm. In the accuracy test results, the recovery percentage (%recovery) was 95.3% and the precision test with the relative standard deviation (%RSD) obtained was 0.85%. The captopril content obtained in the 50 mg captopril tablet sample preparation was 98.0%.